Kesenjangan Kepuasaan Dalam Menyaksikan Berita Pilpres Tahun 2014. (Studi Tentang Uses And Gratification Dalam Menyaksikan Berita Pilpres Tahun 2014 Metrotv Dan Tvone, Dikalangan Mahasiswa Universitas Muhammadiyah Surakarta Angkatan (2012) - Setyawan, Galih Rosa; , Sidiq Setiawan,M.ikom (2016)
Indonesia has two television stations that puts news program, that is metroTV and TVone. Both of them try to get the most audience by making an interesting news program maybe with the presentation of images and uptodate news content. News about presidential election on 2014 ago be a news program that often appear in two televison station. In this research, author wanted to research how satisfied expected, the satisfaction received and satisfaction gap students of Muhammadiyah University class of 2012 in watching the news program presidential electionon 2014 ago in MetroTV and TVone. Therefore, this study uses a model approach uses and gratifications. Samples from this study is the student of 2012 majoring in Communication Studies UMS, citing student of class of 2012 has had the right to vote and also qualified in terms of sorting out their needs in consuming media. Taro Yamane formula used in determining the number of samples in this study, of Rotal 126 students, 56 of them sampled. Therefore, this research usiang a model approach uses and gratification. Data from the research found from spread questionnaire. After data was collected, manaully processing to be interpreted. And then satisfaction gaps calculation performed by the formula discrepancy. From the results data can be seen audience had gratifications sought (GS) high about news shows presidential election 2014 ago are expected can be resolved from both of television station. Associated with gratification obtained (GO) satisfaction respondent level about metroTV average in low level while for TVone in very low level.